2010
DOI: 10.1098/rsbl.2009.0872
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial patterns of sea lice levels on sea trout in western Scotland in relation to fish farm production cycles

Abstract: The relationship between aquaculture and infestations of sea lice on wild sea trout (Salmo trutta) populations is controversial. Although some authors have concluded that there is a link between aquaculture and lice burdens on wild fish, others have questioned this interpretation. Lice levels have been shown to be generally higher on Atlantic salmon farms during the second years of two-year production cycles. Here we investigate whether this pattern relates to lice burdens on wild fish across broad temporal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 12 publications
0
29
0
1
Order By: Relevance
“…Loch Shieldaig is part of the Loch Torridon system, which also includes Upper Loch Torridon and Loch Torridon. Loch Shieldaig was selected because it is relatively small, contains 2 Atlantic salmon farms (consented biomasses of 1375 and 976 t for Farms 1 and 2, respectively) and has been used extensively to study sea lice and their interactions with wild salmonids , Penston et al 2004, 2008a,b, Amundrud & Murray 2009, Penston & Davies 2009, Pert et al 2009, Middlemas et al 2010. The 2 main rivers that flow into the loch system are the Balgy and Shieldaig, which support salmonid populations dominated by Atlantic salmon and sea trout Salmo trutta L., respectively.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Loch Shieldaig is part of the Loch Torridon system, which also includes Upper Loch Torridon and Loch Torridon. Loch Shieldaig was selected because it is relatively small, contains 2 Atlantic salmon farms (consented biomasses of 1375 and 976 t for Farms 1 and 2, respectively) and has been used extensively to study sea lice and their interactions with wild salmonids , Penston et al 2004, 2008a,b, Amundrud & Murray 2009, Penston & Davies 2009, Pert et al 2009, Middlemas et al 2010. The 2 main rivers that flow into the loch system are the Balgy and Shieldaig, which support salmonid populations dominated by Atlantic salmon and sea trout Salmo trutta L., respectively.…”
Section: Study Areamentioning
confidence: 99%
“…A study by Penston & Davies (2009) found that numbers of gravid females on fish farms correlated with the numbers of copepodids in surrounding waters. An increase in sea lice abundance has been linked to an increase in marine mortality of migratory salmonids, and marine salmon farming activities on Scotland's west coast have been implicated as an important contributory factor (Butler 2002, Penston et al 2004, Vøllestad et al 2009, Middlemas et al 2010, Middlemas & Armstrong 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Previous plankton surveys in Loch Torridon (Mc Kibben & Hay 2004, Penston et al 2004, 2008a) and a coupled hydrographic-particle tracking model de veloped for that area (Murray & Gillibrand 2006, Amundrud & Murray 2009) indicate that louse larvae can be trans-ported several kilometres. A study in the Loch Torridon system (and elsewhere) highlighted an apparent link between salmon farming and louse burdens on wild sea trout Salmo trutta L. (Middlemas et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Por otro lado, varios estudios han demostrado que existe una correlación temporal entre los niveles de piojos en las truchas silvestres y el ciclo de producción y biomasa de los peces cultivados en las instalaciones acuícolas adyacentes. A mayor producción acuícola, las poblaciones de truchas presentan mayores niveles de infestación parasitaria (Butler 2002, Marshall 2003, Gillibrand et al 2005, Hatton-Ellis et al 2006, Middlemas et al 2010Arechavala-Lopez et al 2015).…”
Section: Interacciones Entre Piscifactorías Y Los Niveles Parasitariounclassified